Exploring the views of registered nurses caring for spinal cord injury patients in a private rehabilitation hospital in Gauteng - Musie, Maurine Rofhiwa (University of Pretoria, 2023)
Dissertation (MCur (Nursing Science))--University of Pretoria, 2023.